Tail posture and motion as a possible indicator of emotional state in pigs - Groffen, Jordy (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
In the current study, the aim was to investigate whether tail posture and motion can be an indicator of the emotional state of pigs and if the tail posture of the pig is affected by social breeding value (SBV), coping style and/or housing. Emotional state can be defined in two dimensions: valence and arousal. Two batches of 96 finishing pigs were studied in a one generation selection experiment with a 2x2 set up and were housed in a barren or straw bedded pen. In each pen, 6 pigs (3 male, 3 female) were housed. A back-test was done to determine the coping style of the pigs with two categories; high resister and low resister pigs. When possible, each pen held 3 high resisters and 3 low resisters pigs. Furthermore, half of the pens contained pigs with low SBV and the other half contained high SBV pigs. Tail condition scores were determined weekly. A novel environment test (150 sec) with a small arena was performed at 3.5 weeks of age to test the fearfulness of the pigs. Behaviours and vocalisations were recorded together with the tail posture and motion. Four different tail posture and motion categories were recorded; curled tail, hanging tail, tail between legs and tail wagging. Furthermore, home pen observations were performed to link behaviours to a tail posture or motion.